PSYCHOSOCIAL FACTORS PREDICTING PERCEIVED WORKPLACE STRESS AMONG POLICEMEN IN A ZONAL DIVISION - Femi, M, Ilevbare; Adetola, I, Ogunjimi (European Scientific Journal, ESJ, 2014)
The study investigated psychosocial factors as predictors of perceived workplace stress among policemen in a Zonal Division, Ile-Ife of Southwestern, Nigeria. The study adopted a survey research design. A total of one hundred policemen were drawn from the Divisional Headquarters in Moore, Ile-Ife, Osun State comprising 64 males and 36 females within the age range 18 to 52years. Three hypotheses were drawn from the review of literature and tested with appropriate statistical tools. Results using a 2x2x2 Way ANOVA revealed that self-esteem does not have a significant influence on perceived work stress among the policemen (F(1,92)=1.074,P>0.05). Also, there was no significant self-monitoring differences on perceived workplace stress of participants (F (1, 92) =0.017, p>0.05). Further results indicates that locus of control does not have an influence on job stress among participants (F (1, 92) =0.235, P>0.05). Reasons were given why the outcome of this present study negates the outcome of previous studies with emphasis on the socio-political situation experienced by policemen in Nigeria. Recommendation was made with emphasis on the importance of adopting stress-reduction strategies among police officers to improve efficiency at workplace.